Records Committee review for rare bird sighting of Lesser Black-backed Gull on the Iowa River in Iowa City, 1987 - Fuller, James Let al (1987)
Records Committee review of Lesser Black-backed Gull on the Iowa River in Iowa City in Johnson County, IA on January 31, 1987. Includes a record review document with votes and two documentation forms submitted to the committee. Epson - sheet feed